(untitled) (Conference Zone, 2022)
The article analyzes the use and quality of work of machines and equipment for pre-sowing tillage. In terms of tillage, the assumptions for crushing hard materials are considered and the advantages and disadvantages are identified. Based on the analysis, a method for assessing the performance of machines based on the determination of specific kinetic energy in tillage is proposed and the method of determination is described.